Insights into immuno-oncology drug development landscape with focus on bone metastasis - Kähkönen, Tiina E.; Halleen, Jussi M.; MacRitchie, Gary; Andersson, Ronnie M.; Bernoulli, Jenni (Frontiers in Immunology, 2023)
Bone is among the major sites of metastasis in breast, prostate and other major cancers. Bone metastases remain incurable causing high mortality, severe skeletal-related effects and decreased quality of life. Despite the success of immunotherapies in oncology, no immunotherapies are approved for bone metastasis and no clear benefit has been observed with approved immunotherapies in treatment of bone metastatic disease. Therefore, it is crucial to consider unique features of tumor microenvironment in bone metastasis when developing novel therapies. The vicious cycle of bone metastasis, referring to interactions between tumor and bone cells, is well-established but only very recently a novel concept, osteoimmuno-oncology was introduced to the scientific community. Osteoimmuno-oncology emphasizes the significance of interactions between tumor, immune and bone cells in promoting tumor growth, and it can be used to reveal the most promising targets for bone metastasis. In order to provide an insight to current immuno-oncology drug development landscape, we used a renowned cancer drug development resource “1stOncology” to identify novel immunotherapies in preclinical or clinical development for breast and prostate cancer bone metastasis. Currently approved immuno-oncology therapies for breast and prostate cancer were excluded from the search. Based on the database search, 24 immunotherapies were identified in preclinical or clinical development that evaluated effects on bone metastasis. The identified therapies had different targets and modalities, and they were studied as monotherapy or as part of different combinations. From the identified 24 therapies, three therapies were reported with bone metastasis targeting characteristics, one with bone-homing attribute, one with confirmed immune cell survival in hostile bone microenvironment, and one having a rational target in the context for osteoimmuno-oncology. These three therapies were considered among the most promising candidates for bone metastasis in clinical development.